Perilaku Konsumsi Makanan Sebelum dan Saat Pandemi Covid-19 di Masyarakat Perkotaan - Kevin Mangoting; I Gede Agus Widyadana; Debora Anne Yang Aysia (Jurnal Titra, 2022)
Food needs are one of the basic needs that must be met every day. Every society has different habits in meeting food needs. The COVID-19 pandemic has changed the habit of meeting food needs, due to restrictions imposed by the government to reduce the spread of the virus. Changes in habits consist of several things, namely change in food or drink. The purpose of this study was to determine changes in the behavior of urban communities in basic food needs during the pandemic. Questionnaires are used to determine changes in the behavior of urban communities in meeting basic needs. The respondents obtained were 407 respondents from Surabaya and Sidoarjo. The data was analyzed using excel software, and IBM SPSS Statistic 22. The data generated were percentage data from frequency, mean, VR or Variation Ratio, p-value from the results of the kruskall-wallis and mann-Whitney to find out whether there are differences sociodemographic and habits in meeting basic needs. The results showed that the habits of the people of Surabaya and Sidoarjo in meeting basic needs had During the pandemic the change food or drink factor during pandemic people prefer to buy fresh food ingredients and process them into ready-to-eat food